2010
DOI: 10.4314/thrb.v11i4.50172
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovaries and associated clinical and biochemical features among women with infertility in a tertiary hospital in Tanzania

Abstract: The aim of this study was to determine prevalence of polycystic ovaries (PCO) and associated clinical and biochemical features among women with infertility attending gynaecological outpatient department (GOPD) at Muhimbili National Hospital (MNH) in Dar es Salaam, Tanzania. All women with infertility attending the GOPD from 11 th September 2006 to 15 th February 2007 were recruited to the study. Information on socio-demographic, obstetric and menstrual characteristics was collected. Anthropometric measurement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…These findings in partial supported with Pembe & Abeid in Tanzania, who found that the frequency of nulliparous women with PCOS was 62.5%. [54] Also, the present study revealed that 36.0% of women with PCOS had of previous abortion. This is matching with Norman et al, the study in Australia who noted the high-risk of spontaneous-abortion in women with PCOS, and they related this to the high prevalence of obesity and the treatment type they received.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These findings in partial supported with Pembe & Abeid in Tanzania, who found that the frequency of nulliparous women with PCOS was 62.5%. [54] Also, the present study revealed that 36.0% of women with PCOS had of previous abortion. This is matching with Norman et al, the study in Australia who noted the high-risk of spontaneous-abortion in women with PCOS, and they related this to the high prevalence of obesity and the treatment type they received.…”
Section: Discussionsupporting
confidence: 59%
“…[58] In the contract, Pembe et al in Tanzania reported a higher rate of infertility (53.1%) among the studied women with PCOS. [54] Familial clustering of PCOS has been consistently reported suggesting that genetic factors play a role in the development of this syndrome. [59] In the current study, more than one-half of women (62.0%) had a positive family history of PCO syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients in the PCOS group consulted for primary infertility, while the majority in the non PCOS group consulted for secondary infertility. Pembe and collaborators [16] had similar findings. Denakpo and collaborators in Cotonou [13] found spaniomenorrhea, hirsutism and polycystic ovaries as signs with the highest frequency in the PCOS population.…”
Section: Discussionmentioning
confidence: 60%
“…and Australia (Fig. [21][22][23][24][25] This is particularly alarming given the need to improve women's health in the region 26 and the great need to address health disparities globally. 5 In fact, there are no significant data from South America, Russia (i.e., northern Asia), the island countries of Oceania (Melanesia, Micronesia, and Polynesia), or Africa.…”
mentioning
confidence: 99%
“…18,20 An assessment of studies in Africa highlights the lack of research among black women in Sub-Saharan Africa, where there have been no large-scale epidemiologic studies of PCOS and only a very few studies of the PCOS phenotype. [21][22][23][24][25] This is particularly alarming given the need to improve women's health in the region 26 and the great need to address health disparities globally. 27 Furthermore, PCOS among black women may be associated with additional or more severe morbidities, such as uterine leiomyomata, as compared with white women.…”
mentioning
confidence: 99%